2001
DOI: 10.2166/wst.2001.0598
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and problems of sludge pre-treatment processes

Abstract: Pre-treatment processes have been developed in order to improve subsequent sludge treatment and disposal. Disintegration of sludge solids in the aqueous phase changes the sludge structure and solubilizes organic matter. This paper provides an overview of the applications of wet disintegration in wastewater and sludge treatment. Applied disintegration techniques such as mechanical, thermal, chemical and biological methods are briefly described. The methods are compared regarding energy consumption, operational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(96 citation statements)
references
References 0 publications
1
87
0
8
Order By: Relevance
“…The experimental results suggested that the influences of the four pretreatments on the methanogens were different. This was reasonable since the function mechanisms of the four pretreatments on bacteria are different: acid pretreatment are depended on the free H + , alkaline pretreatment depended on the free OH − , thermal pretreatment depended on the high temperature and ultrasonic pretreatment depended on the temperature and the shear produced in the sonication [1,9] . Although there was no methane production in anaerobic fermentation of some sludge samples, the hydrogen consumption also occurred in the last stage of the fermentation because there were other hydrogen-consum- ing functions like homoacetogenesis, sulfate reduction, propionic acid production, and so on.…”
Section: Production Of Methanementioning
confidence: 92%
See 1 more Smart Citation
“…The experimental results suggested that the influences of the four pretreatments on the methanogens were different. This was reasonable since the function mechanisms of the four pretreatments on bacteria are different: acid pretreatment are depended on the free H + , alkaline pretreatment depended on the free OH − , thermal pretreatment depended on the high temperature and ultrasonic pretreatment depended on the temperature and the shear produced in the sonication [1,9] . Although there was no methane production in anaerobic fermentation of some sludge samples, the hydrogen consumption also occurred in the last stage of the fermentation because there were other hydrogen-consum- ing functions like homoacetogenesis, sulfate reduction, propionic acid production, and so on.…”
Section: Production Of Methanementioning
confidence: 92%
“…Some pretreatment methods, such as thermal pretreatment and alkaline pretreatment, have been used to disrupt the microbial cells and release the organics to liquid so as to enhance the anaerobic digestion of sludge [1,8,9] and biohydrogen production of sludge [10][11][12][13][14] . For example, Cai et al [10] utilized alkaline pretreatment to enhance hydrogen production from sewage sludge.…”
mentioning
confidence: 99%
“…SCOD released in the supernatant was found to be in the range 1,100-1,450 mg l -1 . Müller (2001) reported that the solubilization efficiency can be used as an index for the efficiency of sludge disintegration. In the present study, sludge solubilization efficiency (a) was calculated as the ratio of the soluble COD (SCOD) increase by thermochemical pretreatment to the total COD (TCOD) of the sludge before pretreatment as follows:…”
Section: Sludge Disintegration and Sludge Reductionmentioning
confidence: 99%
“…The sludge was put into a 1 L conical flask (D × h = 10 cm × 20 cm) with stopper in the sterilization. Though the optimal temperature of thermal hydrolysis of sewage sludge was 170-175 • C [1,18], higher temperature would consume more energy. So, the conditions of thermal pretreatment were selected as 121 • C, 1.5 atm and 30 min of treatment time accordingly to the references [13,17,19].…”
Section: Sterilization Of Sludgementioning
confidence: 99%